¿Hacia una Nueva Arquitectura Financiera Regional? Problemas y perspectivas de la cooperación monetaria en el ALBA-TCP - Benzi, D.; Guayasamín, T.; Vergara, M. (Revista Iberoamericana de Estudios de Desarrollo)
This paper addresses the experiences of the monetary and financial cooperation carried out within the framework of ALBA-TCP. The first part describes the context of global crisis and emerging multipolarity in which the debate on the reform of the International Financial Architecture (IFA) and regional monetary initiatives are inserted. The second part revises the Latin American initiative of a New Regional Financial Architecture. Later, we analyze the origins, processes and effects of mechanisms implemented within the ALBA-TCP, such as the ALBA Bank and the SUCRE. Finally, the essay concludes by presenting both potential and limitations of these experiences within a regional and global scenario marked by a high degree of uncertainty that, paradoxically so far, seems to delay and inhibit rather than consolidate the strengthening of a New Regional Financial Architecture.